SN 2021dbg: A Luminous Type IIP–IIL Supernova Exploding from a Massive Star with a Layered Shell - Zhao, Zeyi; Zhang, Jujia; Li, Liping; Zhai, Qian; Cai, Yongzhi; Srivastav, Shubham; Wang, Xiaofeng; Lin, Han; Yang, Yi; Filippenko, Alexei V.; Brink, Thomas G.; Zheng, WeiKang (The Astrophysical journal, 2024)
We present extensive observations and analysis of supernova (SN) SN 2021dbg, utilizing optical photometry and spectroscopy. For approximately 385 days following the explosion, SN 2021dbg exhibited remarkable luminosity, surpassing most Type II SNe (SNe II). This initial high luminosity is potentially attributed to interaction between the ejected material and the surrounding circumstellar material (CSM), as evidenced by the pronounced interaction signatures observed in its spectra. The subsequent high luminosity is primarily due to the significant 56 Ni mass (0.17 ± 0.05 M ⊙ ) produced in the explosion. Based on the flux of flash emission lines detected in the initial spectra, we estimate that the CSM mass near the progenitor amounted to ∼(1.0–2.0) × 10 −3 M ⊙ , likely resulting from intense stellar wind activity 2–3 yr preceding the explosion. Considering the bolometric light curve, nebular spectrum modeling, and mass-loss rate, we suggest that the progenitor of SN 2021dbg was a red supergiant (RSG) with a mass of ∼20 M ⊙ and a radius of 1200 R ⊙ . This RSG featured a thick hydrogen shell, which may have contained a region with a sharp decrease in material density, electron density, and temperature, contributing to its layered structure. This object demonstrates mixed features of Type IIP and IIL SNe, making it a transitional event linking the above two subclasses of SNe II.